Social Integration of the Low-income Migrant Population in Beijing Over the Past Two Decades - Mao, Yinquan (International Journal of Social Sciences and Public Administration, 2024)
In order to study the plight of low-income migrant population in Beijing. I have collected data from government websites, reports and papers, to analyze the reason of a large number of low-income migrant population flew out of Beijing. Results manifest that government unkindly policies, unfair educated chances and awful public opinion environment are main factors repelled low-income migrant population. Based on this, Beijing government should issue population kindly policies, ensure the right to education for children of low-income migrant population, and improve public opinion environment. The unfair efforts and rewards reflect the failure of social integration among low-income migrant population in Beijing.